INTERNALIZING THE VALUE OF HONESTY THROUGH STORYTELLING IN INDONESIAN LANGUAGE LEARNING: A CASE STUDY IN ELEMENTARY SCHOOL - Febianty, Adel Listi; Supriyadi (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
The degradation of academic integrity in elementary schools demands a character education approach that touches students' consciousness rather than merely memorizing rules. This study aims to describe the trans-internalization process of honesty values through storytelling within Indonesian language learning. Adopting a qualitative approach with a case study design, this research involved the third-grade homeroom teacher at SDN Waung as the primary subject. Data were collected through participant observation, semi-structured interviews, and document analysis, then validated using source and technique triangulation. Data analysis was conducted referring to the Miles, Huberman, and Saldaña interactive model which includes data condensation, data display, and conclusion drawing. The findings indicate that storytelling successfully integrates three character dimensions simultaneously: cognitive transformation (moral knowing), which concretizes abstract honesty concepts; affective transaction (moral feeling), which fosters empathy and a sense of shame regarding cheating; and behavioral trans-internalization (moral acting), evidenced by a drastic decrease in cheating and increased courage to admit mistakes, replacing fear-based compliance with internal awareness. It is concluded that narrative stories effectively transform cognitive understanding into tangible moral actions by lowering student resistance to moral messages. Theoretically, this study confirms the role of storytelling in reconstructing moral behavior through vicarious learning and narrative transportation mechanisms. Practically, it offers a pedagogical model for teachers to instill character traits enjoyably without rigid indoctrination, whilst simultaneously positioning language learning as a dual strategic vehicle for developing both literacy and student moral integrity.